LC-MS and GC-MS Profiling of Different Fractions of Ficus platyphylla Stem Bark Ethanolic Extract - Madinat Hassan; Sunday Zeal Bala; Musa Bashir; Peter Maitalata Waziri; Ramlatu Musa Adam; Muhammad Abdullahi Umar; Priscilla Kini (Journal of Analytical Methods in Chemistry)
The exploration of medicinal plants in traditional medicine for the treatment of diseases has been practiced for long, globally, because of its cultural acceptability, availability, and affordability. This study investigated the qualitative and quantitative estimation of phytochemicals present in Ficus platyphylla stem bark as well as determined the reducing power and antioxidant property of each fraction against DPPH and NO radicals. The study further elucidated the presence of possible compounds in different fractions (methanol, ethyl acetate, petroleum ether, and chloroform) of Ficus platyphylla stem bark (FPSB) extract using GC-MS, LC-MS, and FTIR techniques. Qualitative phytochemical analysis reveals the presence of phytochemicals: saponin, flavonoids, tannins, phenols, steroids, alkaloids, and glycoside in the ethanolic extract. The LC-MS study of methanol and ethyl acetate fractions reveals the presence of thirteen and three compounds, respectively. GC-MS analysis shows the presence of trans-13-octadecenoic acid as the main compound 38.07% and cis-vaccenic acid as the least compound (0.10%) in the petroleum ether fraction. The main compound in the chloroform fraction is 12-oleanen-3-yl acetate, (3. alpha.) with a peak area percentage of 49.25% and oleic acid been the least compound with 0.07% peak area. The FTIR analysis reveals that the fractions contain compounds with hydroxyl, aromatic, methyl, methylene, methyne, long aliphatic chain, ethers, ether-oxy, peroxides, etc. The analyzed fractions reveal compounds with potential pharmacological activity in the management of pathological conditions.